Degree of conversion of luting resins around ceramic inlays in natural deep cavities: A micro-raman spectroscopy analysis - Lohbauer, Ulrich; Pelka, Matthias; Belli, Renan; Schmitt, J.; Mocker, E.; Jandt, K. D.; Müller, Frank (Operative Dentistry, 2010)
This study evaluated the degree of conversion (Ü) of luting agents around ceramic inlays placed in deep natural cavities. Thirty-six cylindrical Class I cavities (diameter = 4 mm, depth = 4 mm) were prepared in freshly extracted human teeth and randomly divided according to the luting materials used for luting CAD/CAM fabricated inlays (Empress CAD). The dual-cure resin cements Clearfil Esthetic Cement and Variolink II Low and the light-cure composites Grandio Flow and Grandio were luted using the total-etch technique. The self-adhesive dual-cure cements RelyX Unicem and Maxcem Elite were used as recommended by the manufacturer. All of the restorations were photo-activated using a quartz halogen unit (Elipar TriLight; 750 mW/cm2) for 40 seconds. After 24 hour dry-storage in the dark, all the teeth were vertically sectioned into two halves (n=12 per group) using a slow-speed diamond-saw in the bucco-vestibular direction under constant water lubrication to avoid specimen heating. The DC of the luting materials was measured by vibrational spectroscopy using a μ-Raman spectrometer at depths of 1, 3 and 4 mm on each side of the tooth halves (n=24). Disc-shaped samples were produced for measurement of the maximum Ü of each material. Two-way ANOVA and the StudentNewman-Keuls post-hoc test were used in the statistical analysis (α=0.05). All the materials showed no statistical differences in degree of conversion at all tested depths, except for Grandio Flow and Maxcem Elite. Dual-cure and light-cure luting materials showed polymerization homogeneity around ceramic inlays, although dual-cure conventional resin cements tended to show an overall higher conversion.
CRIS-Team Scopus Importer:2023-01-23

Influence of air-polishing devices and abrasives on root dentin-an in vitro confocal laser scanning microscope study - Pelka, Matthias; Trautmann, Siegfried; Petschelt, Anselm; Lohbauer, Ulrich (Quintessence International, 2010)
Objective: To assess the influence of air-polishing devices and various abrasives on flat root surfaces. Method and Materials: A total of 168 natural teeth were embedded in polyurethane resin and treated with airborne-particle abrasion using two air-polishing devices (Prophyflex 3, KaVo; EMS Handy, EMS), four abrasives (Airflow powder, EMS; Cleaning powder, KaVo; ClinPro powder, 3M ESPE; and ProphyPearls, KaVo), and three treatment times (5, 10, and 20 seconds). Defects were quantified using a confocal laser scanning microscope. Results: The Prophyflex device clearly generated deeper substance defects compared to the EMS device, regardless of abrasive used (Kruskal-Wallis, P = .004). ProphyPearls abrasive caused the deepest defects with both devices. ClinPro powder produced the least amount of defects. Defect depths increased significantly for all abrasives with increasing treatment times (Kruskal-Wallis, P = .01), and all abrasives except ClinPro powder caused substantial volume loss. Conclusion: The abrasiveness of air-polishing powders differs depending on the polishing device used. ProphyPearls caused more substance loss than ClinPro powder. © 2010 by Quintessence Publishing Co Inc.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Airborne-particle abrasion; Glycine powder; Nahco3; Prophypearls; Root defects; Root dentin

In vitro wear gap formation of self-adhesive resin cements: A CLSM evaluation - Belli, Renan; Pelka, Matthias; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Dentistry, 2009)
Objectives: To evaluate the depth of wear gaps of new self-adhesive cements after toothbrush abrasion and ACTA wear test. Methods: Luting spaces (325 ± 25 μm width, 2 mm depth) were produced in Empress 2 ceramic blocks with a diamond saw to obtain flat substrate segments for toothbrush abrasion (n = 24) and ACTA wear (n = 27). After etching and silanization, the slits were filled with 8 self-adhesive cements, 2 conventional resin cements and 1 flowable composite, stored for 2 weeks in distilled water at 37 °C and planished to the cement level. Toothbrush abrasion was carried out in a toothbrush simulator (Willytec, Germany) for 20,000 cycles (load 1 N) using an abrasive slurry based on a commercial toothpaste (Elmex, Gaba, Germany, RDA = 77). The ACTA wear experiment was performed following the ACTA protocol in millet seed slurry for 400,000 cycles (Willytec). The gap replicas were measured for vertical wear loss under a confocal laser scanning microscope (CLSM). The data were analyzed using one-way ANOVA and a mod-LSD test at p < 0.05. Results: Toothbrush wear values were lower than the ones obtained for the ACTA wear test for all cements. In the toothbrush test Bifix SE, Clearfil SA, SmartCem 2, G-Cem and Maxcem Elite obtained the highest values together with Grandio Flow. Grandio Flow and AllCem showed to be the most resistant to the ACTA wear test, while SpeedCem the least resistant. No correlation was found between the two wear test experiments. Conclusion: Self-adhesive cements have good wear resistance to toothbrush abrasion but most of them wear more rapidly under higher loads in the ACTA test than conventional resin cements and flowable composites. © 2009 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: ACTA; Cement; Gap; Self-adhesive; Toothbrush; Wear

Leucite-reinforced glass ceramic inlays luted with self-adhesive resin cement: A 2-year in vivo study - Taschner, Michael; Kraemer, Norbert; Lohbauer, Ulrich; Pelka, Matthias; Breschi, Lorenzo; Petschelt, Anselm; Frankenberger, Roland (Dental Materials, 2012)
Objectives: Aim of the present prospective controlled clinical study was to compare the clinical performances of two different cementation procedures to lute IPS Empress inlays and onlays. Methods: Eighty-three IPS Empress restorations (70 class-II inlays, 13 onlays/47 premolars, 36 molars) were placed in 30 patients (19 females/11 males, mean age = 39 years). Two cementation procedures were tested: group 1: forty-three restorations were luted with a self-adhesive resin cement (RelyX Unicem, RX, 3M ESPE); group 2: forty restorations were luted with an etch-and-rinse multistep adhesive (Syntac Classic, Ivoclar-Vivadent) and Variolink II low (SV, Ivoclar-Vivadent). All restorations were evaluated after 2 weeks (baseline = 1st recall = R1, n = 83), 6 months (R2, n = 83), 1 year (R3, n = 82), and 2 years (R4, n = 82) by two independent blinded calibrated examiners using modified USPHS criteria. Results: From R1 to R4, one failure occurred in the SV group (at R2) due to marginal enamel chipping. After 2 years of clinical service (R4), better marginal and tooth integrity (p < 0.05) was found in group 2 (SV) compared to the use of the self-adhesive cement (RX, group 1), while no differences were found for all remaining investigated criteria (p > 0.05). The absence of enamel in proximal boxes (10% with no enamel and 51% of the restorations with less than 0.5 mm enamel width at the bottom of the proximal box) did not affect marginal performance (p > 0.05). Significance: The self-adhesive resin cement RelyX Unicem showed clinical outcomes similar to a conventional multi-step cementation procedure after 2 years of clinical service for most of the tested criteria. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Ceramic; Clinical trials; Inlay; Resin cement; Self-adhesive

Tailoring of physical properties in highly filled experimental nanohybrid resin composites - Pick, Barbara; Pelka, Matthias; Belli, Renan; Braga, Roberto R.; Lohbauer, Ulrich (Dental Materials, 2011)
Objectives: To assess the elastic modulus (EM), volumetric shrinkage (VS), and polymerization shrinkage stress (PSS) of experimental highly filled nanohybrid composites as a function of matrix composition, filler distribution, and density. Methods: One regular viscosity nanohybrid composite (Grandio, VOCO, Germany) and one flowable nanohybrid composite (Grandio Flow, VOCO) were tested as references along with six highly filled experimental nanohybrid composites (four Bis-GMA-based, one UDMA-based, and one Ormocer®-based). The experimental composites varied in filler size and density. EM values were obtained from the "three-point bending" load-displacement curve. VS was calculated with Archimedes' buoyancy principle. PSS was determined in 1-mm thick specimens placed between two (poly)methyl methacrylate rods (Ø = 6 mm) attached to an universal testing machine. Data were analyzed using oneway ANOVA, Tukey's test (α = 0.05), and linear regression analyses. Results: The flowable composite exhibited the highest VS and PSS but lowest EM. The PSS was significantly lower with Ormocer. The EM was significantly higher among experimental composites with highest filler levels. No significant differences were found between all other experimental composites regarding VS and PSS. Filler density and size did not influence EM, VS, or PSS. Significance: Neither the filler configuration nor matrix composition in the investigated materials significantly influenced composite shrinkage and mechanical properties. The highest filled experimental composite seemed to increase EM by keeping VS and PSS low; however, matrix composition seemed to be the determinant factor for shrinkage and stress development. The Ormocer, with reduced PSS, deserves further investigation. Filler size and density did not influence the tested parameters. © 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Elastic modulus; Nanoparticles; Polymerization shrinkage; Resin composite; Shrinkage stress

The distribution of human surfactant proteins within the oral cavity and their role during infectious diseases of the gingiva - Schicht, Martin; Stengl, Christina; Sel, Sadettin; Heinemann, Friedhelm; Goetz, Werner; Petschelt, Anselm; Pelka, Matthias; Scholz, Michael; Rausch, Felix; Paulsen, Friedrich; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2015)
The oral cavity with the teeth and the surrounding gingival epithelium, the periodontium, the salivary glands and other structures are open to the oral environment and thus exposed to multiple microbiological and pathogenic influences. To prevent permanent inflammatory processes such as gingivitis or periodontitis an efficient defense system is essential to ensure healthy and physiological function of the oral cavity and other interacting organic systems. Surfactant proteins (SPs), originally found in pulmonary tissue are important factors of the immune system and beyond this, support the stability and rheology of gas or fluid interfaces. This study aimed to analyze the distribution of surfactant proteins by means of Western blot and immunohistochemistry in salivary glands as well as in healthy and pathological saliva. The different expression patterns of SP-A, -B, -C and -D in healthy and pathological (periodontitis) saliva were determined using ELISA quantification. One further objective of the study was the first detection of two recent discovered proteins belonging to the surfactant protein family within human salivary glands and saliva. The results of the study reveal differences in protein expression of SP-A, -B, -C and -D within healthy and pathologic saliva. The concentration of the surfactant proteins SP-A, SP-C and SP-D is increased in saliva of people suffering from periodontal diseases, whereas by contrast, SP-B shows an opposite expression pattern. Furthermore, the results evidence the presence of SP-G and SP-H within saliva and salivary glands for the first time.
EVALuna2:4399

The effect of air-polishing abrasives on wear of direct restoration materials and sealants - Pelka, Matthias; Altmaier, Katharina; Petschelt, Anselm; Lohbauer, Ulrich (Journal of the American Dental Association, 2010)
Background. Air-polishing devices (APDs) effectively remove supragingival staining. However, the use of APDs on restorative surfaces may result in clinically relevant surface damage and material loss. Methods. The authors made plane specimens (N = 180) of dental restorative materials (Tetric EvoCeram [Ivoclar Vivadent, Schaan, Liechtenstein], Tetric Flow [Ivoclar Vivadent ], Grandio Flow [VOCO, Cuxhaven, Germany], Admira Seal (VOCO], Grandio Seal [VOCO]) and Ionofil Molar [VOCO]). The authors treated the specimens with standardized air abrasion, using three abrasives (Acclean Air Preventive Powder [Henry Schein, Langen, Germany], AirFlow Prophylaxis Powder [EMS, Nyon, Switzerland] and ClinPro Prophy Powder [3M ESPE, Seefeld, Germany]) for 10 seconds each. The authors used profilometric scanning to quantify defect depth and volume loss. Results. The abrasive ClinPro Prophy Powder produced the smallest defect depth and volume loss. Tetric EvoCeram experienced the smallest defect depth, whereas the flowable composites showed the greatest defect depths and volume losses. Sealants showed defects comparable with those the authors found in the glass ionomer, which were significantly smaller than those found in flowable composites. Conclusions. Air polishing of sealants and restorative materials always results in substance loss and surface damage. The sealants performed better in terms of abrasion resistance than did the flowable composites tested. Among the air-polishing abrasives, ClinPro Prophy Powder caused the least abrasive damage. Clinical Implications. Clinicians should use low-abrasion powder for frequent cleaning of discolored restorations with APDs to avoid excessive abrasion of restorative materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Air abrasion; Dental prophylaxis; Dental restoration wear; Dental sealants; Restorative material